Developmental skill exercises for certain types of scoring for the junior aged players (15-16) years basketball - Ali, Ishraq (Journal of Physical Education, 2008)
The aim of this research is to make exercises to develop some types of shooting for basketball, It is notice there is declining in level of performance for attacking skill for this sample and that reflects negative for succession to team, also there is poverty for training program for developing exercises to some types of shooting and that increasing chance of success to get progressive results in league. The research depends on three choices that apply on players of sport club; Adhmiyah .They are (12) players, after getting results and treat them statistically. The research concluded as following: • The developing exercises reflect significantly for some types of shooting for basketball which represents with (shooting, free throwing and shooting with jumping) • There are differences which have statically denoted between post-test and pre test for experience group for side of pre-test for all variables of research.